Pemberdayaan Ekonomi Masyarakat Melalui Pengembangan Usaha Beternak Lebah Trigona Di Sekitar Kawasan Hutan Adat Bayan, Kabupaten Lombok Utara - M. Yusuf; Muji Rahayu; Muhammad Nursan; Sri Supartiningsih; Aeko Fria Utama FR; Dudi Septiadi; Pande Komang Suparyana; Fadli (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
In general, this community service activity aims to increase the knowledge and skills of the farming community through the development of Trigona beekeeping business around the Bayan customary forest area, North Lombok Regency, while the specific objectives are: (1) To develop interest and motivate the people of Bayan Village, Bayan District, North Lombok Regency for entrepreneurship in agriculture and animal husbandry especially beekeeping u trigona; (2) Showing farmers about the technological aspects of trigona beekeeping business; (3) Beekeepers can recognize the socio-economic aspects (sustainable increase in income) of trigona beekeeping business; and (4) Establishing relationships between universities, especially Mataram University with the community. The implementation is carried out using the community development method that emphasizes adult learning (andragogy), involving 8 members of the trigona beekeeper group and students through counseling, demonstrations, and demonstration plots. The results of the implementation show that: (1) This community service activity has been able to increase the knowledge and skills of members of the trigona beekeeper farmer group regarding technical, socio-economic and other aspects related to the development of trigona beekeeping around forest areas; (2) Increase the awareness of farmer group members on the importance of togetherness in a group bond; (3) Demonstrate to the community, especially group members about good, healthy, and environmentally friendly trigona bee cultivation techniques; (2) The response of members of the trigona beekeeper group to extension activities around the Bayan customary forest area, the economy of this dry land farming community is quite high; and (3) This activity has also contributed to the intensification of reciprocal communication between the local government of North Lombok Regency, universities, UNRAM and the community who are members of the trigona honey bee farmer farmer group in Bayan Village, Bayan District, North Lombok Regency.